Stabilisasi Fikosianin Spirulina platensis Dengan Perlakuan Mikroenkapsulasi Dan pH - Endah Saivira Mauliasari; Tri Winarni Agustini; Ulfah Amalia (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Spirulina platensis is a blue-green microalga which is classified into Cyanobacteria. S. platensis is often used as functional food ingredient because their phycocyanin pigment has antioxidant properties. However, the pigment is of low stability and is sensitive to temperature, pH, oxygen, and humidity. The purpose of this study was to determine the effect of microencapsulation and pH treatment on the stability of phycocyanin S. platensis. The experimental design used in the study was Completely Randomized Factorial Design with 2 factors namely microencapsulation process and different pH values (pH 4 and pH 8). The results showed that the microencapsulation process and pH treatment had different effects (P <0.05) on the stability of phycocyanin. S. platensis with microencapsulation at pH 8 produced smaller phycocyanin degradation (5.32±1.37%), antioxidant degradation (38.12±0.31%), and total color different (TCD) (22.1±0.07) compared to other treatments. While the relative concentration (CR) value of the microencapsulated phycocyanin in S. platensis was 94.68±1.37%, higher than that of other treatments. Microencapsulation at pH 8 stabilized phycocyanin by preventing precipitation of the protein.